Resistance Analysis Of Several Antibiotics in Samples of Clinical Isolates With Salmonellosis - Wahyuni, Shohifatul; Pauzi, Iswari; Jiwintarum, Yunan; Fihiruddin, Fihiruddin (Poltekkes Kemenkes Mataram, 2024)
Typhus is a systemic infection caused by Salmonella typhi bacteria, which is usually transmitted through contaminated food or drink, usually treated with antibiotics. Inappropriate use of antibiotics causes various problems, one of which causes resistance. This resistance problem has become a global problem, including in Indonesia where there is an increase in bacterial resistance from 2013 which is 40%, 2016 as much as 60% and in 2019 reached 60.4%, due to irrational use of antibiotics so that bacteria become resistant to drugs. This study aims to determine the description of resistance to several antibiotics in clinical isolates of patients with Salmonellosis This study is a pre-experimental study, with a cross sectional approach. The samples used were pure isolates of Salmonella typhi bacteria obtained from blood samples of Salmonellosis patients, then tested for resistance with 5 different types of antibiotics (Ciprofloxacin, Amoxicillin, Levofloxacin, Cefotaxime and Sulfamethoxazolle-trimethopim) with the disk method (Kearby Beaure). The number of experimental units is 25 units, with the number of replications is 5 replications. The results showed that the five types of antibiotics were sensitive to Salmonella typhi bacteria with the highest antibiotic sensitivity being Ciprofloxacin while the antibiotic that had the lowest sensitivity was Amoxicillin. From the results, it can be concluded that the resistance test of the five antibiotics (Ciprofloxacin, Amoxicillin, Levofloxacin, Cefotaxime and Sulfamethoxazolle-trimethopim) is sensitive.